Confession: Catholics, repentance, and forgiveness in America - Carey, Patrick W. (Oxford University Press, 2018)
Colonial era -- Trent and penance in the colonial period -- Nineteenth century -- The confessional seal: legal and apologetic dimensions of the sacrament of penance -- Sin, repentance, and confession in nineteenth-century American Protestant polemics -- American Catholic theology of penance in nineteenth-century America -- American Catholic practice of confession in nineteenth-century America -- Twentieth century -- History, Pius X, and the practice of confession, 1900-1920 -- Confession, continuity, and reforms, 1920-1960 -- Confession, the new psychology, and birth control, 1920-1960 -- From confession to reconciliation, Vatican II to 2015